Building a new Afghanistan - Rotberg, Robert I. (World Peace Foundation ; Brookings Institution Press, 2007)
"Discusses what Afghanistan and the international community should do to resolve dangerous issues and bolster a still fragile state. Offers a blueprint for moving toward greater democracy and prosperity while arguing that the future success of state building in Afghanistan depends on diversifying the economy and enhancing its economic status"--Provided by publisher.